2000
DOI: 10.1039/b005440m
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric measurements of the interaction of metal complexes with nucleic acids

Abstract: Cyclic voltammetry and differential-pulse voltammetry at mm-sized electrodes were used to measure the decrease in the rate of diffusion of metal complexes upon binding to DNA and to extract the binding constants and effective binding site sizes. A linear correlation was observed between the site size determined electrochemically and the diameter of the complexes [site size: Cu(phen)2(2+) > Fe(phen)3(2+) > Co(bipy)3(3+) approximately Fe(bipy)3(2+) > Ru(NH3)6(3+)]. The binding constants were found to be influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 49 publications
1
34
1
Order By: Relevance
“…The similar difference of association constants in homogeneous solution and interfacial system has also been noted for the complex of Co(phen) 3 3 with dsDNA [22,44]. A value of the association constant was reported to be 1.74 Â 10 3 M À1 for the complex of Co(phen) 3 3 with immobilized dspoly(dG)poly(dc) [22], while 1.6 Â 10 4 M À1 for the complex of Co(phen) 3 3 with double-stranded calf thymus DNA in homogeneous solution was given [44]. Thus, the binding constant between DNA and indicator depends on both the variety of DNA and the experimental conditions such as ionic strength, concentration of indicator or DNA, pH value of solution and the microenvironment, even for a simple model intercalator, MB [36].…”
Section: Dependence Of Peak Currents On Mb Concentrationmentioning
confidence: 60%
See 1 more Smart Citation
“…The similar difference of association constants in homogeneous solution and interfacial system has also been noted for the complex of Co(phen) 3 3 with dsDNA [22,44]. A value of the association constant was reported to be 1.74 Â 10 3 M À1 for the complex of Co(phen) 3 3 with immobilized dspoly(dG)poly(dc) [22], while 1.6 Â 10 4 M À1 for the complex of Co(phen) 3 3 with double-stranded calf thymus DNA in homogeneous solution was given [44]. Thus, the binding constant between DNA and indicator depends on both the variety of DNA and the experimental conditions such as ionic strength, concentration of indicator or DNA, pH value of solution and the microenvironment, even for a simple model intercalator, MB [36].…”
Section: Dependence Of Peak Currents On Mb Concentrationmentioning
confidence: 60%
“…These values are less than the association constant of 6 Â 10 4 M À1 for the complex of MB with double-stranded calf thymus DNA in solution [33] and 3.8 Â 10 6 M À1 for the complex of MB with dsDNA mentioned in the literature [37]. The similar difference of association constants in homogeneous solution and interfacial system has also been noted for the complex of Co(phen) 3 3 with dsDNA [22,44]. A value of the association constant was reported to be 1.74 Â 10 3 M À1 for the complex of Co(phen) 3 3 with immobilized dspoly(dG)poly(dc) [22], while 1.6 Â 10 4 M À1 for the complex of Co(phen) 3 3 with double-stranded calf thymus DNA in homogeneous solution was given [44].…”
Section: Dependence Of Peak Currents On Mb Concentrationmentioning
confidence: 63%
“…A binding ratio is defined as the concentration ratio of the binding ligand to total ligand [6], and the binding number is regarded as the number of participating DNA sites [7]. The interaction of DNA with drugs has been studied by various techniques including fluorescence [8], UV-vis [9], FT-IR [10], luminescence [11], capillary electrophoresis [12], NMR [13], microgravimetry [14], electroanalytical methods [15] and surface plasmon resonance [16]. Voltammetry has also been used to study such interactions [17 -20], and the observed electrochemical signals can provide useful information about the interaction mechanism, binding constant and binding forces.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Several techniques have been employed to study the binding of small molecules to DNA including, for example, viscometry, 10 UV-Vis spectroscopy, 11 isothermal calorimetric titration, 12 luminescence, 13 electrophoresis, 14 fluorescence 15 and electroanalytical methods. [16][17][18][19][20][21] It has been shown that electrochemical techniques have several advantages in measuring the binding of small species to DNA, such as applicability over a wider range of binding constants than classical methods. 16,22 Several authors have shown that the binding constants for redox active species can be obtained from straightforward voltammetric experiments in which the DNA is titrated against the redox active molecule.…”
Section: Introductionmentioning
confidence: 99%